Art Therapy Model To Improve Resilience For Junior High School Students After the Covid 19 Pandemic - Safitri, Safitri Mursyid; Mariyanti, Sulis; Prastyani, Desy; Sudirman, Sudirman (Jurnal Psikologi : Media Ilmiah Psikologi, 2023)
The Covid-19 pandemic that had just passed had a psychological impact on students, such as learning problems, general stress complaints, anxiety complaints, mood swing complaints, anxiety disorders and somatic complaints. This shows that students need inner strength that is able to become a protector , one of which is the resilience . Resilience can be improved through guidance and counseling in schools. It is necessary to do a fun guidance and counseling model that students can accep such as art therapy The purpose of this study is to apply an art therapy model with psychodrama and photo visual media in guidance and counseling in order to increase student resilience. This research method is quantitative with quasi experiment. The experimental designs were resilience pre-test, psychodrama art therapy, group and individual art therapy with photo media, and resilience post-test. Resilience measurement tool based on Grotberg's theory, 42 aitems and coefisient of realibility is 0,915. The sampling technique is non-probability sampling, with 42 respondents from SMP 1945 Jakarta. The results of the paired t test showed that there were differences in student resilience before and after therapy, student resilience became better. Likewise, there are differences in feelings and enthusiasm after doing art therapy. Art therapy through psychodrama and photo visual media is quite effective and can be applied in the implementation of guidance and counseling in junior high schools